Seleksi Hasil Persilangan antara ‘Queen’ dan ‘Smooth Cayenne’ untuk Perbaikan Hasil dan Mutu Buah Nenas - Muhammad Arif Nasution; Roedhy Poerwanto; , Sobir; Memen Surahman; , Trikoesoemaningtyas (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTHybridization program was started in PKBT IPB Bogor in 2003, entangles of 12 parental cultivars, consisting of five type Smooth Cayenne cultivars and seven type Queen cultivars. The cross yielded 195 genotypes with various different character combinations. The result of cluster analysis based on morphological characters showed that there were 33 groups of hybrid at the degree of genetic similarity of 50%. The result of principal component analysis indicated that, between yield component characters and result most importantly, were fruit weight, fruit diameter and fruit length which were main supporting character of variance in hybrid result of the crosses. Descriptive results of fruit yield and quality characters showed three to five classes with the highest number of individuals around the mean value for each character. Fruit weight, crown weight, fruit length, fruit diameter, flesh thickness, core diameter, total soluble solid (TSS), total acid, vitamin C, pH, plant height, and peduncle length, were characters controlled by nuclear genes.Key words : hybridization, variability, Smooth Cayenne, Queen, genotype